Derelictio and Furtum - Vujović, Ognjen (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Abstract: The article analyzes the norms on derelictio and, to an appropriate extent, the norms on usucapio and furtum, which are displyed in Justinian’s Digests and in Gaius’ Institutions. These are related issues, because the acquisition of ownership of a thing through occupatio or usucapio must not ignore the will of the owner of the thing. Of course, if the thing has an owner. Otherwise, it would be a matter of theft, or other types of illegal behavior. The final obstacle keeping someone from acquiring someone else’s thing is the actual will of the owner of the thing. Just as the thing cannot be considered abandoned if the owner has not rejected it of his own free will and in a clear way. The will of the owner to give up the thing (pro derelicto) is mainly reflected in his factual behavior (his inaction) and not in some formal act.